PENDAMPINGAN PENINGKATAN KEMAMPUAN DAN KETELITIAN DALAM MANAJEMEN INVENTARISASI - Ida Ayu Putu Widani Sugianingrat; Mirah Ayu Putri Trarintya; Ni Wayan Alit Erlina Wati; Kadek Candrawati; I Kadek Anom Suardinatha (UNHI Press, 2023)
The existence of office inventory items requires the process of managing, recording, or reporting goods to find out the number of items, additions to existing items and to find out reports of mutations or deletion of goods. The problem that occurs in inventory management at Tiara Dewata is that checking inventory data distributed between departments every 6 months is still not good, there is still a lack of thorough SO inventory officers in each department when checking inventory data between goods that are still good and those that are damaged ( destroyed). Therefore, in order to provide a change from the actual situation that is currently happening and to improve in terms of checking so that it is accurate and in accordance with the data, it is deemed necessary to provide assistance to provide information related to the process of checking inventory data that is correct and in accordance with what is in the company Tiara Dewata. Overall, the assistance activities to increase the ability and accuracy in inventory management in Tiara Dewata's accounting department can be said to be successful. Apart from being measured by the three components above, this success can also be seen from the benefits after participating in the activity. The benefits obtained are being able to carry out inventory management activities better and it is hoped that all parties will always improve accuracy and better communication. So it can be concluded that the purpose of this activity can be achieved